With An Eye On A Set Of New Eyes: Beasts of the Southern Wild - Thomas, Kette (The journal of religion and film, 2013)
This article focuses on how, Beasts of the Southern Wild, represents both divergence and transgression from paradigmatic structures that determine how certain visual representations are to be used. Specifically, the cinematic detours taken by the filmmakers, Lucy Alibar and Behn Zeitlin, do not lead to alien places for most viewers; on the contrary, ancient myths, legends, heroes and prehistoric references are recalled in total isolation from current social and political discourse. In this way, Beasts of the Southern Wild, effectively, highlights mythological structures operating in contemporary American society. Mircea Eliade, Roger Caillois and G.S. Kirk define mythology as a set of narratives that effectively house the sacred, protecting it from the profane, everyday, and temporal activities in life. Thus, this article explores the cultural myths that are disturbed when failure to acknowledge their existence threatens their irrefutable reality. How we think (or should think) reflects certain structural mandates, particularly in the use of representations depicting race, class, or gender. Beasts has been dubbed racist, sexist and elitist by some critiques, the most scathing coming from bell hooks on the representation of a young African-American girl. Because the film enlists the imagination to journey down recognizable mythical trails, interpretations tell us more about the reviewer than it does the film. It is more about what the film “left out” than it is about what the film actually says or does. In this way, I examine bell hooks’ critique alongside the role Toni Morrison’s The Bluest Eye has played in our expectations of representations involving young African-American girls as protagonists.